Antecedents of financial well-being among young working adults: self-control as mediating role / Nor Shahrina Mohd Rafien - Mohd Rafien, Nor Shahrina (2022)
Financial well-being is one of the elements of well-being, which explains individuals’ ability to control their financial matters in their current and future lives without being concerned about their financial situation. Improving the quality of life is important. Therefore, this study aims to analyse the antecedents influencing financial well-being among young working adults. Four variables were tested in this study, namely financial attitude, financial knowledge, financial capability, and parental factor. This study also assessed the mediating effect of self-control on the relationships between financial attitude, financial knowledge, financial capability, and parental factors for financial well-being among young working adults. Furthermore, the theory of family financial socialisation and the strength model of self-control were utilised. The sample for this study consisted of 496 young working adults aged between 18-40 years old, while purposive sampling technique was employed for the participation in the survey among working people in all states in Peninsular Malaysia. A set of questionnaires was distributed through online and physical survey forms to targeted respondents. This was followed by an analysis of the research model using partial least square-structural equation modelling, while Smart PLS 3.0 was used to validate the research model and the proposed hypotheses of the study. As a result, the research findings proved that financial knowledge, financial capability, and self-control support positively influenced the financial well-being among young working adults, although these factors did not have the same influence on financial attitude and parental factors. Based on the mediation analysis, it was found that self-control positively mediated the relationship between financial capability and financial well-being, while self-control had no mediation effect on financial attitude, financial knowledge, and parental factor towards financial well-being. This research has contributed to the literature, particularly in terms of financial well-being among young working adults and the strength of self-control in predicting financial well-being by utilising self-control as a mediator. Self-control has been proven to partially mediate the relationship between financial capability and financial well-being. This study could be utilised as a guide to the related government agencies, such as the Ministry of Education, in the development of financial education programmes at an early age. Given its aim towards better management of financial matters, this study could assist the individuals in understanding the importance of financial well-being, managing financial problems, and sustaining the quality of life.